2014
DOI: 10.1080/07303084.2014.884424
|View full text |Cite
|
Sign up to set email alerts
|

The Ocean as a Unique Therapeutic Environment: Developing a Surfing Program

Abstract: 1The lack of fitness and recreation opportunities for children with disabilities is problematic and 2 can be consequential to proper health and development. All children need to accumulate 60 3 minutes or more of moderate-vigorous intensity activity throughout the day (World Health 4 Organization, 2012). Adapted aquatics offers necessary physical activity and educational 5 programming to children with disabilities and the benefits for children with disabilities are more 6 pronounced and significant than for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 8 publications
1
18
0
11
Order By: Relevance
“…With regard to the first analysis, the results showed positive outcomes as other similar projects shows [5,6,[12][13][14]. Regarding the items related to emotional regulation, most of the participants felt improvements and reported that they did learn about social and emotional competences, what can be a consequence of the fact that surf training was learn alongside with social emotional competencies.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…With regard to the first analysis, the results showed positive outcomes as other similar projects shows [5,6,[12][13][14]. Regarding the items related to emotional regulation, most of the participants felt improvements and reported that they did learn about social and emotional competences, what can be a consequence of the fact that surf training was learn alongside with social emotional competencies.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, it is thought that similar results could be obtained with risk populations in younger children and projects suggestion in the adapted surfing area [5,12,13]. Concerning the impact that this project had in social issues, future interventions should address surf therapy when working with families in vulnerable situations and as a prevention strategy.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Obesity is a public health concern 1 . The prevalence of obesity among U.S. youth aged [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] years is 17% and therefore affects about 12.7 million youth and adolescents 2 . To lower the risk for this and other diseases, it is recommended that children, ages 6-17, accumulate 60 minutes or more of aerobic, muscle strengthening, and bone strengthening physical activity each day, and complete each type of physical activity three times a week 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The instructional goals are to teach each child to paddle, to balance on the board while in various positions, to catch a wave and ride it into shore and lastly to paddle back out through the surf. Each child has their own instructor who formulates individualized instructional goals designed around each child's physical and cognitive needs [8].…”
mentioning
confidence: 99%